Comparing participation patterns in out-of-school activities between Israeli Jewish and Muslim children. (September 2013) - Engel-Yeger, Batya
Abstract: Objectives: (1) To compare participation patterns in out-of-school activities of Israeli Jewish and Muslim children in order to better understand the effect of culture on participation. Methods and results: Participants were 111 Jewish children and 134 Muslim children with typical development, aged between six and 11 years, who completed the CAPE. Muslim children showed significantly higher total participation diversity, and specifically in informal and recreational activities. Muslim children also showed higher participation intensity and higher enjoyment. They performed more activities with someone else and fewer activities in the community. In both cultures, sociodemographic factors including age, gender, parents' education, and familial socioeconomic level were related to the child's participation. Conclusions: Children's participation in out-of-school activities may be related to culture, gender, and other sociodemographic factors. Clinicians should integrate cultural values into therapeutic interventions and consider environmental opportunities or barriers when interpreting participation patterns in order to meet the person's needs and optimize intervention outcomes.